Pengaruh Konseling Asi Eksklusif Terhadap Motivasi Ibu Menyusui Di Ruang Nifas RSUD S.K Lerik Kota Kupang - Djogo, Herliana Monika Azi; Wuladari, Tri Muharni; Letor, Yulia M.K (NHM PRESS, 2022)
Breast milk is considered an ideal nutritional intake for infants because it is safe and contains antibodies that can prevent disease in infants and children. However, until now, two out of three babies in the world do not get breast milk exclusively for six months; this has been the case for two decades. This study aims to determine the effect of exclusive breastfeeding counselling on the motivation of breastfeeding mothers in the postpartum ward of S.K. Lerik Hospital in Kupang City. This type of research is qualitative with a pre-experimental design with a One Group Pretest Posttest design. The sampling technique used was consecutive sampling. The sample size in this study was 32 respondents. Motivation questionnaires were used to measure motivation, while the counselling was given using the Operational standard for Breastfeeding Counseling Procedures based on the exclusive breastfeeding program. Most mothers' motivation before counselling was the negative motivation of 56.3%, and a small proportion of respondents had the positive motivation of 43.8%. Most mothers' motivation after being given counselling was the positive motivation of 84.4%, and only a small proportion of respondents had the negative motivation of 15.6%. The results of the Wilcoxon statistical test in this study showed a change in posttest motivation of 16.50 with a significant p-value of .000. It can be said that there is an effect before and after exclusive breastfeeding counselling on the motivation of breastfeeding mothers in the postpartum room. Health workers, namely nurses and midwives, are expected to improve education for primiparous mothers through counselling.